(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: This paper presents the utilization of phase shifters to manipulate and control the radiation patterns in Uniform Circular Array (UCA) antennas. UCAs, known for their 360-degree coverage and symmetrical radiation patterns, are enhanced by incorporating phase shifters, enabling dynamic beam steering and pattern shaping. Materials and Methods: A uniform circular antenna array operating at 900 GHz frequency has been intended for use in base stations using 4NEC2X simulation software. Results: A single-element dipole antenna having a 2.14 dBi gain is used as a base for constructing a uniform 0.5 λ spacing circular array. The number of elements gradually increased from 2 to 12, raising the gain to 12.3 dBi. HPBW decreased both in vertical and horizontal plans from 80o to 60o and 360o to 20o respectively this implies that the circular array antenna’s directivity is enhanced. The eight-element array beam scanning was performed from 0o to 360o without any distortion in radiation pattern, gain, and directivity, contradictory with the linear array. Conclusions: The studied case and simulation output illustrate the impact of the element numbers and phase shifter configurations on properties of the radiation pattern of the uniform circular array can be obtained when increasing the number of elements, the gain increases too and scanning the main beam without any change and distortion